Energy‐Transfer Modulation for Enhanced Photocatalytic Activity of Near‐Infrared Upconversion Photocatalyst. Issue 1 (27th September 2014) - Zheng, Binbin; Guo, Qiangbing; Wang, Di; Zhang, Hao; Zhu, Yifei; Zhou, Shifeng; Xie, R.‐J.
<x xml:space="preserve">Abstract</x> One of the major challenges of near‐infrared upconversion photocatalyst concerns strengthening the cooperation between Rare‐earth (RE) ions and semiconductor materials for enhancing NIR photocatalytic activity. Herein, the basic energy‐transfer (ET) process between RE ions and semiconductor materials is discussed and the appropriate mode, nonradiative ET, is proposed for efficiently coupling them. As an example, a novel NIR‐based UC photocatalyst, CaIn2O4:Yb3+, Tb3+ was designed and successfully fabricated, which exhibited high photocatalytic activity under 980 nm irradiation. The present report highlights the potential of ET tuning between RE ions and semiconductors toward high performance of NIR photocatalysis.